INTERPERSONAL COMMUNICATION ON LONG DISTANCE RELATIONSHIPS ANALYSIS OF ISLAMIC EDUCATION PSYCHOLOGY IN STUDENTS WHO CARRY OUT REAL WORK LECTURE (KKN) ACTIVITIES - Aditya Lukman; Qoniah Nur Wijayani (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
Student life is often colored by the dynamics of interpersonal relationships, especially for those in long distance relationships (LDR). This study aims to analyze the way interpersonal communication affects the quality of LDR relationships, focusing on the psychological dimensions of Islamic education.  The research methods are qualitative, paradigms and interpretive approaches to phenomenology. Data collection techniques, namely in-depth interviews. The results of this study show that interpersonal communication plays a key role in forming and maintaining LDR relationships of students who are undergoing KKN. Psychological factors such as self-confidence, empathy, and commitment to the values of Islamic Education also influence the dynamics of long-distance relationships. The implications of this research can be used as a basis for the development of educational and counseling programs that support students in managing their LDR relationships more effectively.  Some interpersonal communication strategies are effective in strengthening LDR relationships, such as the use of information technology, wise time management, and the inculcation of spiritual values in daily communication. The practical implications of these findings can be the basis for the development of practical guidance for students undergoing LDR, especially in the context of community service activities in the Islamic Education environment.